(untitled) (TAMADDUN NURI JURNALI, 2025)
This article analyzes the social relations reflected in the works of the poet Berdaq. His works stand out for their depiction of different social strata, human rights, justice, equality, and the people’s concerns. The study examines the social significance of Berdaq’s creativity, his philosophical and humanistic views, and his attitude towards social issues of his time. The article aims to highlight the cultural heritage of the Karakalpak people and the relevance of Berdaq’s works in the modern era.